The Transformation of Education: Democracy and Humanism in Achieving SDGs Amidst Global Challenges and Post-Humanistic Policies - Kaya, Emir; Aydın, Selim; Kaya, Defne (Multicultural Islamic Education Review, 2025)
Global education policies influenced by post-humanism and technocracy risk shifting the focus from democratic and humanist values to technical efficiency. International frameworks, such as those from UNESCO and the OECD, emphasize productivity and technical skills, often at the expense of social values, human rights, and democratic participation. This approach neglects character development and critical thinking, essential for socially aware citizens. To counter this, education policies must align with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 10 (Reduced Inequalities), and SDG 16 (Peace, Justice, and Strong Institutions). Citizenship education should foster awareness of social rights, responsibility, and active participation. SDG 4.7 highlights the importance of inclusive democratic education that promotes diversity, equality, and empowerment. Additionally, integrating social and emotional learning (SEL) enhances collaboration, critical thinking, and respect for differences, reinforcing democratic societies. By aligning education with SDG targets, policymakers can ensure that education fosters ethical leadership, civic engagement, and sustainable social development. This approach underscores the need for policies that balance quantitative outcomes with character formation, building a more inclusive and democratic future